The process of cancer. Part I. The role of selected factors in the induction of carcinogenesis - Jopkiewicz, Sylwia Paulina (Journal of Education, Health and Sport, 2019)
SummaryIntroduction and objective: Cancer arises from genetic and epigenetic changes in the cell. Indication of the direct causes of cancer is no doubt very difficult, because the process of carcinogenesis is a multi-level and multi-stage. Knowledge of existing threats to health is a determinant in making everyday decisions that are crucial in minimizing the risk for precancerous and cancerous. Featured Review article is only an outline of selected factors participate in the induction of neoplastic process. Its aim is to present the concept and the process of carcinogenesis, and to discuss the participation of selected factors in the induction of neoplastic lesions.Description of knowledge: Preiniciation is a period in which the carcinogenic effect on normal cells. Initiation is related to the appearance of the first permanent changes in the genetic material of the cell. The promotion is the stage in which the diseased cells grow and multiply. However, in the progression of metastasis occurs it. Factors that are surrounded by human impact on the integrity of the genetic material. Many of them have been scientifically proven effect mutogenne and carcinogenic.Conclusions:The effects of interactions of carcinogens accumulate in different time intervals. Carcinogens interact with DNA, causing deterioration or change in its structure. They can also cause changes in gene expression. Carcinogenic for a human body may be the same ingredients, food products and substances in food preservatives. Some viruses can be oncogenic due to the integration of the viral genome into the host genome in the vicinity of proto-oncogenes. Exposure to heavy metals and their metabolites contribute to DNA damage.